The Role of Pronunciation in the Competency-based English Curricula of Algerian Middle and Secondary Schools - bouchair, Zahia (Journal of Human Sciences, 2018)
The present study attempts to explore the degree of compatibility between middle and secondary school teachers’ practices in the teaching and assessment of pronunciation and the principles of Competency-Based Language Teaching. To achieve this goal, two questionnaires have been designed and implemented to 87 middle and 62 secondary school teachers. In addition, a representative sample of official exams at both levels has been analysed. The analysis of the results revealed that the existence of a big discrepancy between pronunciation teaching and assessment practices of the respondents at both levels and the principles of competency-based language teaching.